2012
DOI: 10.1152/ajpheart.01180.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sustained therapeutic hypercapnia attenuates pulmonary arterial Rho-kinase activity and ameliorates chronic hypoxic pulmonary hypertension in juvenile rats

Abstract: Jankov RP. Sustained therapeutic hypercapnia attenuates pulmonary arterial Rho-kinase activity and ameliorates chronic hypoxic pulmonary hypertension in juvenile rats. Am J Physiol Heart Circ Physiol 302: H2599 -H2611, 2012. First published April 13, 2012; doi:10.1152/ajpheart.01180.2011.-Sustained therapeutic hypercapnia prevents pulmonary hypertension in experimental animals, but its rescue effects on established disease have not been studied. Therapies that inhibit Rho-kinase (ROCK) and/or augment nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…We have recently shown that chronic exposure to hypoxia promotes pulmonary hypertension in newborn rats via the Rho kinases pathway (30). In our study, we observed significant ROCK activation in hyperoxia-treated male pup lungs but not their third-generation pulmonary arteries.…”
Section: Articlessupporting
confidence: 56%
See 2 more Smart Citations
“…We have recently shown that chronic exposure to hypoxia promotes pulmonary hypertension in newborn rats via the Rho kinases pathway (30). In our study, we observed significant ROCK activation in hyperoxia-treated male pup lungs but not their third-generation pulmonary arteries.…”
Section: Articlessupporting
confidence: 56%
“…Lung tissue and third-generation intrapulmonary arteries were lysed in radioimmunoprecipitation assay buffer, and protein samples (50 μg/ lane) were blotted, as previously described (30). Myosin phosphatase target subunit 1 (MYPT-1) is one of the substrates of ROCK.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological studies. Lungs from six animals from each group (3 from each of 2 separate litters) were air-inflated and perfusion-fixed at constant pressure, embedded in paraffin, sectioned, and immunostained for CD68 (to identify macrophages), or were stained with hematoxylin-eosin, or for elastin, as previously described (23,29,33,35). For all analyses, measurements were carried out on four noncontiguous left lung sections per animal by an observer blinded to group identity.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded inflated lung tissue sections were stained with hematoxylin and eosin (for lung morphometry), Hart's elastin (for the arterial medial wall area), or Picrosirius Red (to identify collagen), as previously described (23,26,33,42,43). To localize NOS2 or to assess an indicator of oxidative/ nitrative stress, sections were immunostained for NOS2 or 3-nitrotyrosine, respectively (22,23).…”
Section: Animal Interventionsmentioning
confidence: 99%